Radiological dimensions of the Eustachian tube in patients with adhesive otitis media. Issue 5 (11th May 2023) - Alanazy, S; Kim, H; Nam, G-S; Kim, H C; Cho, S I
Abstract: Objective: This study aimed to analyse the computed tomography parameters for effective ventilation in patients with adhesive otitis media. Methods: Twenty-six patients with unilateral adhesive otitis media were included in the study. The patients' temporal bone computed tomography images were retrospectively reviewed. Eustachian tube length and diameter were measured. Mastoid pneumatisation and middle-ear size were evaluated by measuring petroclival and Eustachian tube–tympanic cavity ventilation angles. Results: The average Eustachian tube length was 38.4 mm and 38.9 mm in adhesive otitis media and healthy ears, respectively. The Eustachian tube diameter of the adhesive otitis media ears (1.47 mm) was significantly narrower than that of the healthy ears (1.83 mm). There were no significant differences in the angles between adhesive otitis media and healthy ears. Conclusion: A narrow Eustachian tube diameter was associated with developing adhesive otitis media. Measuring Eustachian tube diameter is simple and can be routinely performed when examining temporal bone computed tomography images for Eustachian tube function evaluation.